2021
DOI: 10.1186/s12864-021-07999-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of full-length mitochondrial genomes of five Skeletonema species reveals conserved genome organization and recent speciation

Abstract: Background Skeletonema species are prominent primary producers, some of which can also cause massive harmful algal blooms (HABs) in coastal waters under specific environmental conditions. Nevertheless, genomic information of Skeletonema species is currently limited, hindering advanced research on their role as primary producers and as HAB species. Mitochondrial genome (mtDNA) has been extensively used as “super barcode” in the phylogenetic analyses and comparative genomic analyses. However, of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 76 publications
2
8
0
Order By: Relevance
“…The two HAB species S. marinoi and S. pseudocostatum diverged approximated 16 Mya (95% HPD 5.66-29.85 Mya), which was consistent with results estimated previously using 18S rDNA (about 14 Mya) (Sorhannus, 2007). The divergence time estimated in this study among Skeletonema species was generally similar or slight large than that estimated based on the mtDNA PCGs, indicating the clock rate was similar across the two organelles (Liu et al, 2021). This study provided the divergence time among the Skeletonema species based on the cpDNAs for the first time.…”
Section: Skeletonema Species Divergence Time Estimation Based On Cpdnassupporting
confidence: 90%
See 3 more Smart Citations
“…The two HAB species S. marinoi and S. pseudocostatum diverged approximated 16 Mya (95% HPD 5.66-29.85 Mya), which was consistent with results estimated previously using 18S rDNA (about 14 Mya) (Sorhannus, 2007). The divergence time estimated in this study among Skeletonema species was generally similar or slight large than that estimated based on the mtDNA PCGs, indicating the clock rate was similar across the two organelles (Liu et al, 2021). This study provided the divergence time among the Skeletonema species based on the cpDNAs for the first time.…”
Section: Skeletonema Species Divergence Time Estimation Based On Cpdnassupporting
confidence: 90%
“…The phylogenetic analysis supported that S. pseudocostatum and S. tropicum could clustered into sister clade in agreement with the topology in recent studies using 18S rDNA, 28S rDNA, and cox1 gens (Kooistra et al, 2008;Yamada et al, 2017). However, the topologies of the phylogenetic trees were not identical, the tree using the cpDNA PCGs obtained in this study was very similar with the tree based on 28S rDNA (Kooistra et al, 2008;Yamada et al, 2017), and was almost identical with the cox1 tree (except the positions of S. costatum and S. grevillei) (Liu et al, 2021), but was different from the tree based on 18S rDNA (Yamada et al, 2017), confirming that these different genes can have incongruent histories.…”
Section: Phylogeny and Selection Patterns Within Skeletonema Cpdnassupporting
confidence: 90%
See 2 more Smart Citations
“…Khaw et al ( 2020 ) reported 18S rDNA priming as a simple method for cultured eukaryotic microalgae identification. Also, mitochondrial and chloroplast genomes were efficient in phylogenetic analyses and comparative genomic analyses of coastal diatoms (Liu et al 2021a , b ). Kobayashi et al ( 2014 ) referred to the multiple sequence alignment of heat shock protein and the phylogenetic tree of some algae as well as their protein and cDNA expression patterns determining the survival threshold temperature in Cyanidioschyzon merolae and Chlamydomonas reinhardtii .…”
Section: Introductionmentioning
confidence: 99%